Prevalence of Enterobius vermicularis among children in Iran: a comprehensive systematic review and meta-analysis - Moussavi, Elnaz; Houssaini, Mohammad; Salari, Nader; Hemmati, Mahvan; Abdullahi, Ahmad; Khaleghi, Ali Asghar; Shohaimi, Shamarina; Mohammadi, Masoud (Elsevier, 2023)
Background: Parasitic infections are among the most common diseases worldwide, and enterobiasis is a well-known type of parasitic infection in children. Given the existence of several reports on the prevalence of Enterobius vermicularis in different provinces of Iran and the heterogeneity of the reported prevalence data, this study aims to investigate the overall prevalence of Enterobius vermicularis among children in Iran through a systematic review and meta-analysis. Methods: This systematic review and meta-analysis study involved a comprehensive search of several databases, including PubMed, ScienceDirect, SID, and Google Scholar, focusing on cross-sectional studies that examined the prevalence of Enterobius vermicularis infection in Iranian children. The identified studies were entered into the EndNote software for review. The quality of observational studies was evaluated using the STROBE checklist. The information extracted from the studies was entered into the Comprehensive Meta-analysis (CMA, Version 2) software. Heterogeneity among the studies was analyzed using the I2 test, and publication bias was assessed using the Egger test and funnel plot. Results: A total of 51 studies, with a sample size of 46,070 children, were included in the review. Using the random effects method, the overall prevalence of Enterobius vermicularis among children in Iran was determined to be 6.7 (95CI: 5.2–8.6). The review of the factors affecting study heterogeneity and sample size indicated that as sample size increased, the prevalence of Enterobius vermicularis among children in Iran also increased (p = 0.578). Additionally, with an increase in the year of conducting the studies, the prevalence of Enterobius vermicularis among children in Iran decreased (p < 0.05). Conclusion: The findings of this study show a relatively high prevalence of Enterobius vermicularis among children in Iran. We recommend health policymakers recognize the significance of this issue and take necessary measures to reduce the incidence of this infectious agent in children, implementing more effective preventive measures through mass media and educational campaigns.